Dynamic Changes of Sp6 Transgene Expression in Dental Epithelial Cells during Long-term Culture - Trianna W. Utami; Keiko Miyoshi; Hiroko Hagita; Ryna D. Yanuaryska; Taigo Horiguchi; Takafumi Noma (The Indonesian Journal of Dental Research, 2011)
To investigate the function of specificity protein 6 (SP6) transcription factor by gain-of-function procedure, we established cytomegalovirus (CMV) promoter-driven Sp6 stable transformants, C9 cells, using dental epithelialderived cells. Initially, C9 cells produced a significant amount of SP6 protein. However, SP6 expression was reduced in these cells upon long-term culture. We could detect Sp6 transcripts in C9 cells by RT-PCR throughout the passages, although the CMV promoter is known to be epigenetically silenced. We recently found that SP6 was a short-lived protein that was degraded by a ubiquitin-independent proteasome pathway, although it is yet unclear how Sp6 expression was regulated during culture. Thus, we studied the possibility of epigenetic regulation of Sp6 expression. Comparative analysis of endogenous and exogenous Sp6 mRNA expressions demonstrated the specific down-regulation of exogenous Sp6 mRNA levels during culture passages. A DNA methyltransferase inhibitor, 5-Aza-2'-deoxycytidine (5AC), and a histone deacetylase inhibitor, valproic acid (VPA), enhanced or induced SP6 protein expression up to passage 28 without enhancing the mRNA level. The dramatic up-regulation of exogenous Sp6 mRNA was uniquely observed only at passage 50 by 5AC or VPA treatment. These findings indicate that multiple epigenetic regulatory mechanisms operate to fine-tune Sp6 expression during long-term culture.